Studies of multifunctional Bi₁₂GeO₂₀ compound synthesized by chemical route - Kumar, Anup; Verma, Manish Kumar; Jena, Biswajeet; Tiwary, Dhanesh; Singh, Narsingh; Mandal, K. D. (SPIE, 2024)
Increasing water pollution poses a serious threat to both humankind and animals in the current situation. Low cost optical especially photocatalytic material is of utmost relevance to improve situation and meet the global energy demand with little environmental damage. The aim of this study is to develop low-cost low temperature reproducible method to synthesize multifunctional material suitable for degradation of a very dangerous water contaminant dye under visible light exposure. A semiwet chemical route was used to synthesize a multifunctional Bi₁₂GeO₂₀ compound suitable for photocatalytic activity for the degradation of Rhodamine B (RhB) dye under visible light exposure. Bi₁₂GeO₂₀ (BGO) ceramic with polycrystalline structure was prepared successfully e using a low temperature chemical process. X-ray powder diffraction reveals that single-phase BGO ceramic was formed. Nanosized BGO ceramic particles that had been stabilized, XRD and TEM to showed particle sizes in the 60–10 nm range. Due to the favorable band gap (2.72 eV) and the sillenite type Bi₁₂GeO₂₀ exhibits strong photocatalytic activity for the degradation of Rhodamine B (RhB) dye under visible light exposure.
SPIE 13059, Smart Biomedical and Physiological Sensor Technology XXI, 1305904 (6 June 2024)